Visuospatial information transfer and task self-assessment within and between autistic and non-autistic adults - Charlotte E. H. Wilks; Sarah J. Foster; Michelle Dodd; Sue Fletcher-Watson; Martin Lages; Danielle Ropar; Noah J. Sasson; Catherine J. Crompton (PLoS ONE, 2025)
Previous research has demonstrated that autistic people transmit verbal information as effectively as non-autistic people; however, when autistic and non-autistic people interact less information is transmitted. We tested whether these findings generalised to a task requiring the transmission of primarily visual information and examined how accurately participants self-assessed their performance. 310 adults (154 autistic) were allocated to one of three, six-person diffusion chain conditions: (i) autistic, (ii) non-autistic, (iii) mixed autistic and non-autistic. Participant 1 in each chain watched a video of an experimenter creating a dog shape from a puzzle toy that could be manipulated. Participant 1 showed Participant 2 how to make a dog shape, Participant 2 showed Participant 3, and so on until the end of the chain. Objective Performance was scored as the number of puzzle pieces in the correct location; self-assessment was measured on a 100-point scale, and the similarity of this self-assessment was calculated by comparing it to Objective Performance. Analyses indicated no difference in the amount of information transmitted between autistic, non-autistic, or mixed chains, or in self-assessment ratings and the similarity of these. Both autistic and non-autistic participants shared information with others and evaluated their performance similarly, aligning with previous work on the transmission of verbal information. However, the predicted breakdown in information sharing in the mixed chains did not occur. It is possible that a mismatch in neurotype may not impact information transmission that is less-verbal and more visuospatial. The heterogeneity of the sample may also have overshadowed any effect of neurotype.